IMPLEMENTATION OF WORLD CLASS MANUFACTURING INTO THE MANAGEMENT SYSTEM BUSINESS PROCESSES OF THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The necessity to have a variety of management tools results from the need to develop competitive strategies in order to build a strong market position and make fast decisions. World Class Manufacturing (WCM) is an example of a management model that solves these problems. WCM implements methods and tools that allow an organization to achieve competitive advantage based on the principle of creating high-quality products at a low price.The global goal of WCM is to meet the requirements and needs of individual consumers, suppliers of material recourses and other partners in industrial cooperation, shareholders and each individual employee, as well as all other concerned parties, groups, institutions and society as a whole. There are the following target guidelines: cost minimization, maximization of quality, speed and flexibility of changes, sustainability of the current operation and development.The WCM model is based on the tools such as Total Quality Control, Total Productive Maintenance, Total Industrial Engineering and Just in Time.The pledge to success of WCM is the conscious attitude of personnel to the process of organizational changes, based on the philosophy of continuous improvement. The development of this awareness takes place through the workers’ knowledge resulting in a change in thinking and action.The WCM model is based on the interdependence of 10 components (pillars) that characterize manufacturing processes and controls, such as Safety-S, Cost Deployment-CD, Focused Improvement-FI, Autonomous Maintenance-AM, Professional Maintenance - PM, Quality Control-QC, Logistic & Customer Service - L & CS, Early Equipment Management-EEM, Early Equipment Management-EEM, People Development - PD, Environment - E.Investigation of a considerable range of different sources devoted to the processes of implementation of WCM in the business processes in the West and East makes it possible to determine the typical steps of its implementation. They are diagnosing, formulation of development goals and strategic priorities, transition to the operation on the principles of WCM, institutionalization of WCM and monitoring.Successful implementation of WCM is accomplished through three interrelated areas, such as the use of WCM tools; optimization of the organizational model of the enterprise and the change of managerial culture.
Keywords: World Class Manufacturing, high quality, low price, Safety-S, Cost Deployment-CD, Focused Improvement-FI, Autonomous Maintenance-AM, Professional Maintenance - PM, Quality Control-QC, Logistic & Customer Service - L & CS, Early Equipment Management-EEM, Early Equipment Management-EEM, People Development - PD, Environment-E, Total Quality Control, Total Productive Maintenance, Total Industrial Engineering, Just in Time.